THE MECHANISM OF DEVELOPMENT OF THE EPIDEMIC PROCESS IN SALMONELLOSIS - Matnazarova Gulbakhor Sultanovna; Saidkasimova Nargiza Sayfullaevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Аnnotation: In the last twenty years, in large numbers of countries in the world, the epidemiological features of the incidence of salmonellosis have increased, in particular, human morbidity rate, infection farm animals and birds with salmonella, and the environmental harmed has increased by S. Enteritidis. The increase in the epidemiological significance of farm animals, birds and industrial poultry products, the connection between epizootic and epidemic processes, the changes in the sanitary and epidemiological service in the Republic of Uzbekistan require the restructuring of the existing system of epidemiological surveillance for salmonellosis.